2019
DOI: 10.24820/ark.5550190.p010.827
|View full text |Cite
|
Sign up to set email alerts
|

New series of ɣ-pyrone based Podands: synthesis, characterization and study of their application in acetate salts cation trapping in nucleophilic substituted reactions

Abstract: Dialkyl 4-oxo-4H-pyran-2,6-dicarboxylates are synthesized via esterification of chelidonic acid or via intramolecular cyclization of dialkyl-2,4,6-trioxoheptanedioates. Reaction of the dialkyl 4-oxo-4H-pyran-2,6dicarboxylates with a variety of glycol monoalkyl ethers produces a series of new podands in good yields. To demonstrate the use of these podands in cation trapping, nucleophilic substitution reactions are carried out with various acetate salts. The results indicate that the cation diameter's compatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Although the second method has been described in the literature, in our hands, it has given unsatisfactory results. Therefore, optimization of the cyclization was carried out (see the Supporting Information), and it was found that the most favorable conditions are refluxing in toluene with p -toluenesulfonic acid (5 mass % relative to triketone 1 ) with addition of EtOH to increase the solubility of the starting triketone 1 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the second method has been described in the literature, in our hands, it has given unsatisfactory results. Therefore, optimization of the cyclization was carried out (see the Supporting Information), and it was found that the most favorable conditions are refluxing in toluene with p -toluenesulfonic acid (5 mass % relative to triketone 1 ) with addition of EtOH to increase the solubility of the starting triketone 1 .…”
Section: Resultsmentioning
confidence: 92%
“…At the first stage, we had to develop a convenient and easily scalable method for the synthesis of diethyl chelidonate 2 from the commercially available diethyl acetonedioxalate ( 1 ) (Scheme ), which, in turn, can be obtained based on the well-known Claisen condensation of diethyl oxalate and acetone in the presence of sodium ethoxide . In the literature, we were able to find two methods for the synthesis of diethyl ester 2 , , including a two-stage approach through the formation of chelidonic acid, which is further esterified by refluxing in EtOH saturated with HCl, or direct acid-catalyzed cyclization of ester 1 . The first method gave diethyl chelidonate ( 2 ) from chelidonic acid in only ∼25% yield because of ineffective esterification of both CO 2 H groups.…”
Section: Resultsmentioning
confidence: 99%